2019
DOI: 10.1002/fsn3.1075
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional properties of Lactobacillus plantarum strains WiKim83 and WiKim87 as a starter culture for fermented food

Abstract: This study aimed to evaluate the safety (hemolysis and enzyme activity), probiotic properties (gastrointestinal tract tolerance, adhesion, hydrophobicity, and auto‐aggregation), and functional characteristics (antimicrobial, antioxidant, and β ‐galactosidase activities) of lactic acid bacteria (LAB), isolated from kimchi, in order to select a multifunctional LAB strain for starter culture in fermented food. The five isolated strains included Lactobacillus plantarum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…All the four isolates including standard probiotic strain resisted 0.5% ox-bile, while, OBK05 showed a significant ( p <0.05) difference in tolerance (6.97 and 6.35 CFU/mL) with other isolates at 2 and 4 h ( Table 2 ). The obtained results are in accordance with previous studies where the probiotic strains isolated from rumen liquor showed similar viability [ 38 ], and Lactobacillus strains isolated from kimchi showed similar viability in bile salts [ 39 ]. The obtained results suggested OBK05 as the most promising strain to tolerate low pH and high bile concentration compared to other LAB isolates.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…All the four isolates including standard probiotic strain resisted 0.5% ox-bile, while, OBK05 showed a significant ( p <0.05) difference in tolerance (6.97 and 6.35 CFU/mL) with other isolates at 2 and 4 h ( Table 2 ). The obtained results are in accordance with previous studies where the probiotic strains isolated from rumen liquor showed similar viability [ 38 ], and Lactobacillus strains isolated from kimchi showed similar viability in bile salts [ 39 ]. The obtained results suggested OBK05 as the most promising strain to tolerate low pH and high bile concentration compared to other LAB isolates.…”
Section: Resultssupporting
confidence: 91%
“…The obtained values are higher than the previous reports where the probiotic P . pentosaceus Wikim 85 and Wikim 86 showed 32% and 29% antioxidant activity, respectively [ 39 ]. The present findings are in agreement with [ 33 ] and [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adhesion results on Caco-2 and HT-29 cells demonstrated the potent adhesion capacity of L. brevis MYSN105 to the gastrointestinal tract. Previous reports have shown that adhesion of Bifidobacterium and Lactobacillus strains to intestinal mucus plays an important role in Enteropathogen exclusion ( Collabo et al, 2005 ; Jung et al, 2019 ). Therefore, the antimicrobial activity exhibited by L. brevis MYSN105 provides a competitive inhibition of pathogenic microbes in the colonic environment.…”
Section: Discussionmentioning
confidence: 99%
“…The genomic finding suggests that understanding the functional and genetic characteristics could provide new insights into applications in gut health and animal feed additives ( Heo et al, 2018 ). These attributes make L. brevis MYSN105 an attractive probiotic candidate ( Jung et al, 2019 ) for industrial applications.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the carbon source, common activities of enzymes were observed for Lactobacillus spp., such as β-galactosidase being responsible for lactose hydrolysis, β-glucosidase impacting the ability of Lactobacillus spp. to endure higher temperatures and breaking glycosidic bonds, acid phosphatase helping to obtain energy from phosphates, or naphthol-AS-BI-phosphohydrolase being responsible for alkaloids, nucleotides, and proteins dephosphorylation [43][44][45][46][47]. In addition to that, all of the strains lack the activity of potentially harmful enzymes, like β-glucuronidase-which is associated with toxic, mutagenic, and carcinogenic potential-as well as chymotrypsin, which is associated with GIT diseases [47,48].…”
Section: Discussionmentioning
confidence: 99%